Análisis del comportamiento en las exportaciones de aguacate hass y su mejor destino internacional (2022)
In this research, we will highlight the benefits that have made the Hass avocado one of the most desired products worldwide, such as the increase in Colombian exports, which makes it a competitive fruit, so much so that it leads non-traditional orders, especially in Europe and abroad. United States, and in turn as producers, analyze the best destination for our product.